Comportamientos emergentes en la solución distribuida de problemas colectivos: una aproximación desde la educación (Papeles, 2012)
This article aims to characterize emergent behaviours in a group of students whilst solving problems collectively within a classroom at a public school. Distributed cognition and distributed problem solving are the main constructs that lead the characterization of the emergency inside a group of people. Related to the methodology, team-building games and experiments design are the meditational artefacts used to identify interaction patterns and explain how the multiagent system carries out reconfigurations and reaches results, as well as, how the system identifies elements in the distributed problem solving, such as, coherence or modularity among others. Lastly, the results show five emergent behaviours in the process of solving problems collectively which are associated with its main components: coherence, modularity and competence.
Keywords: distributed cognition; distributed problem solving; emergency in multiagent systems; team-building activities